Fashion Trend Visualization Through AI-Based Illustration: A Case Study on Fashion Trend Forecast 2025/2026 Strive Book - Enrico (ULTIMART Jurnal Komunikasi Visual, 2025)
Digital technology has evolved and brought significant changes in various aspects of the creative industry, including the fashion industry. One of the innovations that is now starting to be applied in the visualization process, especially in producing fashion illustrations, is artificial intelligence (AI) technology. Through a case study on Fashion Trend Forecast 2025/2026 STRIVE book, this research aims to analyze how AI technology compares with manual and digital illustrations in communicating ideas and narratives of fashion trends. The method used in this research is a descriptive qualitative approach to visual analysis based on the main aspects of stroke line, color, proportion, and composition. The results show that AI-based fashion illustration is able to display visuals with high quality and detail, but it needs to be supported by prompt experiments to achieve the intended image results. The efficiency of the process to produce illustrations is also very significant, because no hand-draw sketch skills are required. It can be concluded that AI has great potential as a tool in the visualization process of fashion trend books, especially in conceptualizing and communicating trend elements quickly and adaptively. Keywords: visualization; fashion trend; illustration; artificial intelligence (AI)